1998
DOI: 10.1017/s1357729800009668
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high fat diets on the performance and food intake of primiparous and multiparous rabbit does

Abstract: The influence of high fat diets on several production traits of primiparous and multiparous rabbit does was studied in 246 lactations from a total of 61 crossbreed rabbit does (Californian × New Zealand). Starting with a control diet (diet C) with 26 g ether extract (EE) per kg dry matter (DM), two isoenergetic diets were formulated adding fat from vegetable sources up to 99 g EE per kg DM (diet V) or animal sources up to 117 g EE per kg DM (diet A). Digestible energy/digestible protein ratio (DE/DP) was maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
0
11

Year Published

2003
2003
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 12 publications
8
27
0
11
Order By: Relevance
“…Literature dealing with intake regulation in the young rabbit is scarce, and often in disagreement. Thus, works of Pascual et al (1998 and led to similar conclusions as ours. Increasing the energy concentration of diet using starch (Pascual et al, 1999) or lipids (Pascual et al, 1998) led to a lower consumption of solid diet by young rabbits between 22 and 35 days of age.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Literature dealing with intake regulation in the young rabbit is scarce, and often in disagreement. Thus, works of Pascual et al (1998 and led to similar conclusions as ours. Increasing the energy concentration of diet using starch (Pascual et al, 1999) or lipids (Pascual et al, 1998) led to a lower consumption of solid diet by young rabbits between 22 and 35 days of age.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, works of Pascual et al (1998 and led to similar conclusions as ours. Increasing the energy concentration of diet using starch (Pascual et al, 1999) or lipids (Pascual et al, 1998) led to a lower consumption of solid diet by young rabbits between 22 and 35 days of age. On the contrary, other studies suggested that the regulation of the solid feed intake in young rabbits would implicate other mechanisms than the level of the digestible energy.…”
Section: Discussionsupporting
confidence: 88%
“…Despite the change in milk composition according to the stage of lactation [18][19][20] that we did not consider in our calculations, nutrient intake differed in quantity and quality, according to weaning age. Classical-weaned rabbits ate more crude protein and fat than early-weaned rabbits, whereas crude energy intakes were similar.…”
Section: Feed Intake and Body Growthmentioning
confidence: 95%
“…After a 7 d adaptation period, faeces were collected individually for 4 d (from 13 to 16 d of lactation) as recommended by Perez et al (1995). The faeces collection period was fixed from 13 to 16 d of lactation in order to find the maximum milk yield and feed intake regularity (Pascual et al, 1999;Maertens et al, 2006). From the moment the doe rabbits were placed in metabolic cages, both feed intake and milk yield were monitored on a daily basis.…”
Section: Experimental Procedures Lactating Doesmentioning
confidence: 99%